Rock Metamorphosis by Kinetic Energy - Robert G. Bednarik (Ital Publication, 2019)
The objective of this work was to test the hypothesis that weathering-resistant surface layers found in intensively hammered petroglyphs at many sites worldwide and on other heavily battered metamorphosed rocks are the result of kinetic energy-induced tribological reactions. The methods of material testing included extensive fieldwork and in-situ studies at an Indian site that had been subjected to fluvial battery in the distant geological past; the removal of numerous surface and subsurface samples; and their analysis by several laboratory methods. These included binocular light microscopy, scanning electron microscopy, thin sectioning and elemental composition determination of crucial sites. It was confirmed that samples show evidence of crystallization by ductility of formerly amorphous silica cement in quartzite, yielding a tectonite of fully crystalline quartz. This finding confirms that the surficial application of very high levels of kinetic energy to certain rock types that are susceptible to metamorphosis can yield exceptionally weathering-resistant surface layers. This phenomenon has not been described before. Although it was first observed in rock art it is now thought to occur much more widely in numerous geological contexts, such as at fault mirrors, in the form of what has been regarded as glacial polish and on ventifacts.